A Numerical Study on the Critical Height of Embankments Supported by Geotextile Encased Granular Columns. (2016) - Carreira, Marta; Almeida, Márcio; Pinto, Alexandre
Abstract: The present work describes two-dimensional finite element analyses carried out to study the critical height of an embankment supported by geotextile encased granular columns (GEC) in a very soft soil, using PLAXIS 2D software. Comprehensive numerical analyses were performed, by increasing the height of the embankment, to study the influence of the tensile stiffness of the encasement, the compressibility and thickness of the soft clay layer and the span between columns, in order to assess the embankment critical height. It was concluded that the diameter and the spacing between columns are the only parameters affecting the development of the critical height. Based on the numerical results obtained, a design equation was proposed to estimate the embankment critical height, function of the mesh configuration, column diameter and spacing between columns. It was also possible to compare the equation developed, with the available critical height results for piled embankments, concluding that there are no significant differences between the two.